Coaching and feedback in the exercise periods of advanced studio voice lessons (Orfeu, 2018)
The aim of this paper is to characterise the interaction between teacher and student as they engage in vocal teaching and learning in the exercise periods of advanced studio lessons. An expert voice teacher was observed in one-to-one lessons with six undergraduate students, and films of their lessons are described and interpreted in terms of collaborative behaviour, with special reference to coaching and feedback. The findings describe procedures that are highly instructive, with the teacher dominating verbal dialogue and directing the students’ activity, along with multimodal procedures in which the teacher draws on verbal, vocal and gestural communication to scaffold student learning. It is argued that the complex and challenging nature of advanced vocal studies gives rise to specialist practices that should be approached and understood on their own terms.